Polychaete assemblages in a tropical hypersaline coastal lagoon of the southeastern Gulf of Mexico during the rainy season - Dávila-Jiménez, Yasmín (2019)
Introduction: The Río Lagartos lagoon, located in the Ría Lagartos Biosphere Reserve, Yucatán, Gulf of Mexico, is a coastal hypersaline system ca. 80 km long (east-west). It comprises three basins: western (close to Río Lagartos fishermen village), middle (Las Coloradas) and eastern (close to El Cuyo fishermen village), that communicate through very narrow natural channels. Despite several studies have been performed on the vertebrate fauna, the aquatic invertebrates, and especially polychaetes, remain largely unknown. Objective: The objective of this study is to describe the composition and distribution of the benthic polychaete community, and to analyse potential environmental drivers. Methods: The biological material was collected in 16 stations distributed along the lagoon during the rainy season (September 2017). Two replicates per station were obtained using a Ponar standard dredge or cores (6” diameter). Environmental variables such as grain size, organic carbon content in the sediments, and salinity, among others, were measured. Results: A total of 827 specimens belonging to 26 species and 16 families were identified. Of these, 23 species are new records for the Río Lagartos lagoon. Community composition changed between the different basins associated with strong gradients in salinity, subaquatic vegetation (algae and seagrasses) proportions in the samples and grain size. No polychaetes were recorded at the easternmost basin (El Cuyo basin), where salinity was between 67-80 psu. In the rest of the lagoon, the distribution of polychaetes was heterogeneous, especially near the mouth (western basin), where the highest and lowest density, species richness and diversity were recorded. The highest density was found at station 6, where dense algal mats of the genus Avrainvillea dominated. The families Syllidae and Nereididae were the most abundant and widely distributed families in the lagoon. The species Syllis lagunae and Nereis pelagica dominated the western basin and Prionospio heterobranchia and Sphaerosyllis taylori dominated the middle basin. Conclusions: The salinity records associated with some species were well above the top limits previously reported, establishing the euryhaline character of many species in the region.